Selonsertib Inhibits Liver Fibrosis via Downregulation of ASK1/ MAPK Pathway of Hepatic Stellate Cells - Yoon, Young-Chan; Fang, Zhenghuan; Lee, Ji Eun; Park, Jung Hee; Ryu, Ji-Kan; Jung, Kyung Hee; Hong, Soon-Sun (Biomolecules & therapeutics, 2020)
Liver fibrosis constitutes a significant health problem worldwide due to its rapidly increasing prevalence and the absence of specific and effective treatments. Growing evidence suggests that apoptosis-signal regulating kinase 1 (ASK1) is activated in oxidative stress, which causes hepatic inflammation and apoptosis, leading to liver fibrogenesis through a mitogen-activated protein kinase (MAPK) downstream signals. In this study, we investigated whether selonsertib, a selective inhibitor of ASK1, shows therapeutic efficacy for liver fibrosis, and elucidated its mechanism of action and . As a result, selonsertib strongly suppressed the growth and proliferation of hepatic stellate cells (HSCs) and induced apoptosis by increasing Annexin V and TUNEL-positive cells. We also observed that selonsertib inhibited the ASK1/MAPK pathway, including p38 and c-Jun N-terminal kinase (JNK) in HSCs. Interestingly, dimethylnitrosamine (DMN)-induced liver fibrosis was significantly alleviated by selonsertib treatment in rats. Furthermore, selonsertib reduced collagen deposition and the expression of extracellular components such as α-smooth muscle actin (α-SMA), fibronectin, and collagen type I and . Taken together, selonsertib suppressed fibrotic response such as HSC proliferation and extracellular matrix components by blocking the ASK1/MAPK pathway. Therefore, we suggest that selonsertib may be an effective therapeutic drug for ameliorating liver fibrosis.